Analysis and modeling of laser diodes for WDM system - Liu, Hairong (2008)
Semiconductor laser diodes play a crucial role in the success of optical communication systems due to the fact that they are coherent light sources. There are several types of laser diodes such as Fabry-Perot laser diodes, distributed feedback laser diodes and vertical cavity surface emitting lasers, etc. In optical fiber communication systems, one of the most important characteristics required for a semiconductor laser is the stable mode operation featured by high side-mode-suppression-ratio (SMSR) and narrow spectral linewidth. In conventional Fabry-Perot lasers, the feedback of radiation into the active medium is accomplished by the reflective facets.